Maternal hemoglobin concentrations across pregnancy and child health and development from birth through 6–7 years - Young, Melissa F.; Nguyen, Phuong; Tran, Lan Mai; Khuong, Long Quynh; Tandon, Sonia; Martorell, Reynaldo; Ramakrishnan, Usha (Frontiers in Nutrition, 2023)
Background: The role of changes in maternal hemoglobin (Hb) across pregnancy on child health and development (CHD) remains unclear. Objective: We examined the association between maternal Hb trajectories and CHD outcomes: a) birth outcomes (birth weight, length, gestational age, preterm and small for gestational age); b) child Hb at 3, 6, 12 and 24 mo; and c) motor and mental development at 12 and 24 mo and cognitive functioning at age 6-7 y. Methods: We used data from a randomized controlled trial (PRECONCEPT) conducted in Vietnam (N=1175 women enrolled during preconception with offspring follow-up through 6-7 y). Maternal Hb trajectories were developed using latent class analysis with Hb data at preconception, early (≤20 wks), mid (21-29 wks), and late (≥30 wks) pregnancy. Multivariable linear and logistic regression models were used to assess the association between maternal Hb trajectories on CHD outcomes, adjusting for confounding variables at the maternal, child and household levels. Results: Four distinct maternal Hb trajectories were identified. Track 1 (low initial Hb-decline) was associated with lower child Hb at 3 mo (β [95%CI] -0.52 [-0.87, -0.16]), 6 mo (-0.36 [-0.68, -0.05]), 12 mo (-0.46 [-0.79, -0.13]) and 24 mo (-0.44 [-0.72, -0.15]) and motor development at 12 mo (-3.58 [-6.76, -0.40]) compared to track 4 (high initial Hb-decline). After adjustment for multiple testing, relationships remained robust with the exception of associations with child Hb at 6 mo and motor development at 12 mo. Track 2 (low initial Hb-improve) was the only Hb trajectory to increase across pregnancy; however, it was insufficiently powered. Track 3 (mid Hb-decline) was associated with lower child Hb at 12 mo (-0.27 [-0.44, -0.10]) and 24 mo (-0.20 [-0.34, -0.05]) compared to track 4 (high initial Hb-decline). Maternal Hb trajectories were not associated with birth outcomes or child development at 24 mo or 6-7 y. Conclusion: Maternal Hb trajectories during pregnancy are associated with child Hb concentrations across the first 1000 days, but not with birth outcomes or later cognitive functioning. More work is needed to better understand and interpret changes in Hb levels during pregnancy especially in resource poor settings.